The RaT technique for concurrent test of dinamically reconfigurable hardware - Manuel G. Gericota (2000)
A new class of FPGAs that enable partial and dynamic reconfiguration has been recently introduced into the market, opening exciting possibilities for dynamically reconfigurable hardware systems. While enabling concurrent reconfiguration without disturbing system operation, this technology also raises a new test challenge: the reconfiguration process can activate faults which would otherwise not be visible. This paper proposes a structural concurrent test method that reuses the IEEE 1149.1 infrastructure, exploiting the same dynamic and partially reconfigurable features underlying this test challenge.